PERAN PPATK DALAM UPAYA ANTI PENCUCIAN UANG DAN PENCEGAHAN PENDANAAN TERORISME DITENGAH COVID-19 (STUDI KASUS TREN TIPOLOGI PENCUCIAN UANG TAHUN 2020) - Muhammad Wahid Murniawan (Universitas La Tansa Mashiro, 2021)
This research is motivated by the rampant crime of money laundering (TPPU) that occurs in Indonesia and the conditions of the anti-money laundering and prevention of terrorism financing (APU PPT) regime. One of the institutions that are members of the APU PPT regime is the Financial Transaction Analysis Reporting Center (PPATK) which acts as the Financial Intelligence Unit (FIU) in Indonesia. This study aims to analyze the role of PPATK in AML-CFT efforts amid COVID-19 by considering the new trend of money laundering typology. This research was conducted with a qualitative method using snowball sampling in data collection. So as to get the findings of research on the role of INTRAC in accordance with Law no. 8 of 2010 in the aspect of AML and CFT efforts and the role of the PPATK is able to produce the latest money laundering typology data, including responses to dealing with money laundering typology trends that will emerge in the future. And the results show that the role of PPATK in receiving reports and analyzing reports on information related to money laundering is the largest contributor to the identification of money laundering typologies and the role of PPATK in dealing with the impact of the pandemic in 2020 shows rapid adaptation and response both in terms of public services and performance in the prevention and eradication of money laundering.